Efficacy and Safety of Different Energy Settings for Atrial Fibrillation Ablation using the Duty-cycled Radiofrequency Ablation Catheter (PVAC) - Lönnerholm, Stefan; Malmborg, Helena; Blomström, Per; Blomström-Lundqvist, Carina (Journal of Cardiovascular Medicine and Cardiology, 2014)
<p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">In recent years, new ablation catheters have been developed to facilitate atrial fibrillation (AF) ablation procedures, including the multi-electrode pulmonary vein ablation catheter (PVAC), capable of using different proportions of unipolar and bipolar energy. The purpose of this study was to evaluate the acute efficacy, as well as safety, when using the two different energy settings for the PVAC catheter. <p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"><strong style="box-sizing: border-box; outline: none; font-weight: bold; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px;">Methods and Results: Thirty-five patients with a mean age of 62 ± 7.7 years with paroxysmal (54%) or persistent AF were included in the study and randomized to 4:1 versus 2:1 bipolar/unipolar energy setting with the PVAC device. The mean number of applications with the PVAC catheter was 41 ± 10 and 51 ± 15 (p = 0.3) respectively with the 4:1 and the 2:1 setting. Touch-up with another RF ablation catheter was necessary in 3 and 7 patients respectively in the 4:1 and 2:1 group. The procedure time was 155 ± 35 and 174 ± 41minutes respectively and the total fluoroscopy time, including the time for touch-up with another catheter, was 42 ± 14 and 50 ± 17 minutes respectively with the 4:1 versus 2:1 setting. No complications were seen in any group. <p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"><strong style="box-sizing: border-box; outline: none; font-weight: bold; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-stretch: inherit; line-height: inherit; font-family: inherit; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px;">Conclusion: There was no significant difference between the 4:1 and 2:1 bipolar-to-unipolar energy setting with the PVAC regarding the number of applications needed to create (PVI), the number of patients in which (PVI) could be achieved without touch-up applications, the procedure time or the fluoroscopy time.